SIMULASI KINERJA RANGKAIAN POWER DECOUPLING TIPE BUCK-BOOST UNTUK MEMPERKECIL DIMENSI KAPASITOR DC LINK DALAM SISTEM PROPULSI KERETA API - Hansel Daerendra Mahardhika Elsam; Waru Djuriatno; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
This research explains the rectifier system in a train propulsion system that uses a capacitor as a filter (referred to as a DC link capacitor), which generally has a large capacitance and requires the addition of a power decoupling circuit to assist the capacitor in energy storage. The power decoupling circuit is connected in parallel between the rectifier system and the load side, and the topology used is a buck-boost type. The circuit consists of several components such as capacitors, inductors, and switch components (MOSFETs). The objective of this research is to obtain a small capacitance value for the DC link capacitor by using a power decoupling circuit. Testing is carried out using Simulink software in MATLAB as a simulation tool to control the power decoupling circuit and enable energy storage. In this research, testing is also conducted on the rectifier system without using the power decoupling circuit to determine the comparison of capacitor capacitance values used between the two systems. The results obtained in this study are as follows: for the system without using a power decoupling circuit, it requires a DC link capacitor of 70 µF. On the other hand, the system that uses a power decoupling circuit requires a DC link capacitor of 2 µF, with the same resistive load of 100 Ω. This is achieved by adding a decoupling capacitor of 10 µF and a decoupling inductor of 1mH in the power decoupling circuit. Keywords: Performance, Buck-Boost Power Decoupling, Capacitor, Propulsion System.